MEMBANGUN PREDIKSI TERCERAHKAN TENTANG MASA DEPAN DAKWAH LINTAS AGAMA - Zalikha Zalikha (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Islam considers human being as the most perfect and noble creature from another God's creatures. Perfection and glory are not only from the structure of creation but also from the presence assuming the Caliphate ability. Humans